2015
DOI: 10.1080/19381956.2016.1218583
|View full text |Cite
|
Sign up to set email alerts
|

Microchimerism of male origin in a cohort of Danish girls

Abstract: Male microchimerism, the presence of a small number of male cells, in women has been attributed to prior pregnancies. However, male microchimerism has also been reported in women with only daughters, in nulliparous women and prepubertal girls suggesting that other sources of male microchimerism must exist. The aim of the present study was to examine the presence of male microchimerism in a cohort of healthy nulliparous Danish girls aged 10-15 y using DNA extracted from cells from whole blood (buffy coats) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Remarkably, studies of women without sons have identified detectable male microchimerism. One study that explored male microchimerism in a population of nulliparous 10–15‐year‐old Danish girls found 13.6% to have male microchimerism in their peripheral blood, supporting the findings of 13% prevalence previously found in healthy nulligravid women (Muller et al, 2015; Yan et al, 2005). We do not know if male chimerism originated from an older brother with fraternal DNA passed through the mother, male miscarriages, vanishing twins, transfusion history or sexual intercourse (de Bellefon et al, 2010; Dierselhuis et al, 2012; Muller et al, 2015; Peters et al, 2019; Utter, Reed, Lee, & Busch, 2007; Yan et al, 2005).…”
Section: Human Studiessupporting
confidence: 59%
See 1 more Smart Citation
“…Remarkably, studies of women without sons have identified detectable male microchimerism. One study that explored male microchimerism in a population of nulliparous 10–15‐year‐old Danish girls found 13.6% to have male microchimerism in their peripheral blood, supporting the findings of 13% prevalence previously found in healthy nulligravid women (Muller et al, 2015; Yan et al, 2005). We do not know if male chimerism originated from an older brother with fraternal DNA passed through the mother, male miscarriages, vanishing twins, transfusion history or sexual intercourse (de Bellefon et al, 2010; Dierselhuis et al, 2012; Muller et al, 2015; Peters et al, 2019; Utter, Reed, Lee, & Busch, 2007; Yan et al, 2005).…”
Section: Human Studiessupporting
confidence: 59%
“…One study that explored male microchimerism in a population of nulliparous 10–15‐year‐old Danish girls found 13.6% to have male microchimerism in their peripheral blood, supporting the findings of 13% prevalence previously found in healthy nulligravid women (Muller et al, 2015; Yan et al, 2005). We do not know if male chimerism originated from an older brother with fraternal DNA passed through the mother, male miscarriages, vanishing twins, transfusion history or sexual intercourse (de Bellefon et al, 2010; Dierselhuis et al, 2012; Muller et al, 2015; Peters et al, 2019; Utter, Reed, Lee, & Busch, 2007; Yan et al, 2005). Research by Kamper‐Jørgensen et al in a comprehensive study of numerous reproductive traits, health and lifestyle did not establish a model‐based prediction of male microchimerism and concluded there is little known about the relationship between exposure to allogeneic cells and maintaining persistent chimerism; although, histocompatibility with transgenerational HLA relationships has been suggested and should be further investigated (Kamper‐Jorgensen et al, 2012).…”
Section: Human Studiessupporting
confidence: 59%
“…Prior studies demonstrated male microchimerism being present in 13.6% of adolescent girls (Muller et al , 2015) and 13.3% of healthy null gravid women (Yan et al , 2005). Potential sources for the male cells are considered to be transfusion (Utter et al , 2007), older brothers (or discontinued male pregnancies from their mother) (Dierselhuis et al , 2012), unrecognized male miscarriages (Yan et al , 2005), vanishing twins (de Bellefon et al , 2010), or possibly sexual intercourse without pregnancy (Muller et al , 2015). The significant difference in our study, in favor of the control group, suggests that a substantial proportion of the microchimerism could be explained by unrecognized pregnancies or the harboring of microchimeric cells after sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that recognition of transfused cells as foreign by the recipient immune system was eliminating such cells within a few days . The case of bidirectional blood exchanges between mother and fetus during pregnancy could be considered equivalent to transfusion, particularly maternal transfusion to fetus who, because of the immaturity of their immune system, become tolerant to maternal nucleated cells . Along the same line of reasoning, we hypothesized that young children transfused for severe anaemia, particularly related to primary malaria infection, would equally be relatively immunodeficient and susceptible to transfusion‐related microchimerism.…”
Section: Discussionmentioning
confidence: 99%